Tailoring geopolymer mix to attain desired fire-protection - Wong, Keng Khang (2017)
Geopolymer has been heavily investigated and researched due to its potential on thermal appliances over the years. In this research, three sets of geopolymer admixtures, namely different mixed alkali (K,NaK,Na), different Al/Na ratio (Al/Na = 0.55, 0.69, 1.04, 1.12, 1.15), different Si/Al ratio (Si/Al = 1.03, 1.25, 1.5, 1.75, 2), have been synthesized to attain desired fire-protection properties. Mechanical strength, Dilatometry, SEM, TGA, XRD and FTIR tests have been carried out on each set of admixtures to investigate their respective thermal performance. Experiments showed that the major factors affecting mechanical strength evolution were dehydration and sintering densification. Sodium geopolymer (Na) possessed a larger degree of shrinkage at elevated temperature due to dehydration. Crack formation due to dehydration adversely affected strength performance whereas densification increased strength when exposed to 500℃. Sodium geopolymer possessed denser structure and higher mechanical strength compared to potassium geopolymer (K) due to sintering when exposed to 900℃. Mixed alkali geopolymer (NaK) had intermediate strength performance between K and Na. Geopolymer with larger w/solids ratio experienced a larger degree of shrinkage and more crack formation. XRD and dilatometry results revealed that excess alkali (Al/Na=0.55,0.69) caused the formation of nepheline at approximate 700℃ which led to serious mechanical strength loss. Metakaolin based geopolymer (Si/Al = 1.03, 1.25, 1.5, 1.75, 2) experienced larger degree of shrinkage at elevated temperature. Abundant cracks formation and nepheline formation of metakaolin geopolymers resulted in severe strength loss after high temperature exposure.